2021
DOI: 10.1108/ijlss-09-2020-0139
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrated learning: creating a company-specific production system (XPS)

Abstract: Purpose Companies create company-specific production systems (XPS) by tailoring generic concepts to fit their unique situation. However, little is known about how an XPS is created. This paper aims to provide insights into the creation of an XPS. Design/methodology/approach A retrospective case study was conducted in a Norwegian multinational company over the period 1991–2006, using archival data and interviews. Findings The development of the XPS did not start with a master plan. Instead, dispersed existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Findings indicated that the NCC spent 15 years developing its XPS, and this process might be sorted into four main phases (Hekneby et al, 2021b):…”
Section: Creation Of the Company-specific Production Systemmentioning
confidence: 99%
“…Findings indicated that the NCC spent 15 years developing its XPS, and this process might be sorted into four main phases (Hekneby et al, 2021b):…”
Section: Creation Of the Company-specific Production Systemmentioning
confidence: 99%
“…Organization-level studies attempt to explain how concepts are adopted, adapted and used within organizations, as well as their impact (e.g. Hekneby et al, 2022;McCann et al, 2015).…”
Section: Organization Concepts Retention and Revitalizationmentioning
confidence: 99%
“…However, some studies have questioned this notion of abandonment, showing that concepts may instead become dormant (Røvik, 2011) or continue to influence organizations by exerting a lasting influence on their discourses, control systems and ideologies (Heusinkveld and Benders, 2012). More active retention is observed in studies in which organizations make concepts work by adapting content and learning from experience (Ansari et al, 2014;Hekneby et al, 2022). However, what motivates these significant efforts to bring about the performance improvements promised by concepts remains unclear.…”
Section: Revitalizing An Organization Conceptmentioning
confidence: 99%
See 2 more Smart Citations